Assessing greenhouse gas emissions in a primary care subdistrict in Cederberg, South Africa - Schwerdtle, Patricia; Quitmann, Claudia; Herrmann, Alina; Thakur, Sanskrithi; Adams, Claire; Jobanputra, Kiran; Mash, Robert (BMC health services research, 2025)
Climate change poses a significant threat to global health, risking decades of progress in public health gains and threatening the ability of developing countries to achieve universal health care goals. In response, healthcare systems worldwide are beginning to assess and mitigate their environmental impacts, ideally alongside building their resilience to climate change. Most of this work has centred on high-emitting health systems in high-income countries, yet a large number of developing countries are also committed to reducing the environmental impact of health care and in doing so pursuing a clean development trajectory. This study evaluates the emissions of a primary healthcare network in the Cederberg subdistrict, South Africa, using a standardized greenhouse gas accounting tool. The findings aim to inform mitigation strategies for Cederberg and may offer insights to other resource-constrained settings.
Veröffentlicht: 22. Oktober 2025
Gesehen am 04.12.2025